Emerging technology to measure habitat quality and behavior of grouse: examples from studies of greater sage‐grouse. (5th June 2017) - Forbey, Jennifer Sorensen; Patricelli, Gail L.; Delparte, Donna M.; Krakauer, Alan H.; Olsoy, Peter J.; Fremgen, Marcella R.; Nobler, Jordan D.; Spaete, Lucas P.; Shipley, Lisa A.; Rachlow, Janet L.; Dirksen, Amy K.; Perry, Anna; et al.
Abstract : An increasing number of threats, both natural (e.g. fires, drought) and anthropogenic (e.g. agriculture, infrastructure development), are likely to affect both availability and quality of plants that grouse rely on for cover and food. As such, there is an increasing need to monitor plants and their use by grouse over space and time to better predict how changes in habitat quality influence the behavior of grouse. We use the greater sage‐grouse Centrocercus urophasianus to showcase how new technology can be used to advance our understanding of the ecology, behavior and conservation of grouse. We demonstrate how laser, spectral and chemical detectors and unmanned aerial systems can be used to measure structural and phytochemical predictors of habitat quality at several spatial scales. We also demonstrate how advanced biotelemetry systems and robotic animals can be used to measure how habitat quality influences fine‐scale habitat use, movement and reproductive effort of grouse. Integrating these technologies will allow researchers to better assess and manage the links among habitat quality (safety and food), resource acquisition (foraging behavior) and reproductive behaviors of grouse.